Weed Science in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Akobundu. I O, 1987. Weed Science in the Tropics - Principles and Practices. Wiley-lnterscience. 522 pp ISBN 0-471-915440